PERAN ETIKA PROFESI DAN HUKUM PERBURUHAN DALAM MEMBANGUN MOTIVASI DAN PRIBADI UNGGUL MAHASISWA JURUSAN TEKNIK MESIN STTI BONTANG - Irianto; Santoso (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
This research aims to reveal the role of professional ethics and labor law in shaping the motivation and personal excellence of students majoring in Mechanical Engineering at the Bontang College of Industrial Technology (STTI). Professional ethics and labor law have an important role in guiding students to develop high motivation and superior personal character during their studies. This research uses qualitative methods with in-depth interviews and document analysis as data collection techniques. The research respondents were active students majoring in Mechanical Engineering at STTI Bontang. The research results show that understanding professional ethics provides a moral foundation for students to develop positive professional attitudes. Meanwhile, knowledge of labor law provides a better understanding of rights and obligations in the employment context. These two factors positively influence student motivation to achieve academic excellence and self-development. Apart from that, professional ethics and understanding of labor law also contribute to the formation of students' personal character, including integrity, responsibility, and awareness of rights and justice. Students who understand the values ​​of professional ethics and labor law tend to have higher intrinsic motivation and develop superior personalities. This research provides a better understanding of the important role of professional ethics and labor law in guiding students majoring in Mechanical Engineering to achieve superior motivation and personal character. The implications of the results of this research can be used as a basis for developing more holistic and sustainable educational programs in higher education institutions.